Acute norovirus gastroenteritis in up to five years children highly rotavirus-vaccinated population in southern Brazil (Research, Society and Development, 2022)
The acute gastroenteritis remains a problem social, economic and of the public health of the global impact and among the main causative agents are the viruses. This study aimed to show the circulation of rotavirus (RoV) and norovirus (NoV) infections in children under 5 years, vaccinated or not against RoV, enrolled in the health system presented gastroenteritis. From March 2011 to February 2012 a total of 160 stool samples were collected, overall positivity rates were 11.9% (19/160) for NoV and was not found infected patients with RV. The children include had a mean of 2.8 and a median of 3 years of old, and the average of rotavirus vaccination rate was 83.85%. This result shows that this circulating NoV and suggests a reduction in the occurrence of RoV infection in children with high vaccination coverage rate.